Analisis Retention Time Terhadap Pemisahan Fasa Pada Three Phase Separator di Unit Lube Oil Complex (LOC) III - Devfara, Muhammad Farel; Abror, Hadziqul; Triono, Agus (Petroleum Engineering, Faculty of Engineering, University of Jember, 2024)
This research analyzes the retention time of the three phase separator in separating oil, water, and gas phases at PT Pertamina refinery unit IV Cilacap. With an initial retention time ranging from 31 - 34 minutes, there are phases that are still not separated in the separator. This study aims to provide recommendations for retention time based on unseparated phases and how to apply them to the separator at the refinery. This study involves three types of lube oil analyzed, namely DAO, MMO, and LMO. The results show that there is still a difference between the phases at the inlet and outlet which indicates that the phase separation at the initial retention time is still not optimal so that new retention time recommendations need to be made. In the type of DAO lube oil with a retention time of 33 minutes with the largest difference at the inlet and outlet of 0.040. In the type of MMO lube oil with a retention time of 31.2 minutes with the largest difference of 0.037. In the type of LMO lube oil with a retention time of 34.2 minutes with the largest difference of 0.036. After making retention time recommendations based on the results of the difference between inlet and outlet, the retention time recommendations for DAO are 54.6 minutes, MMO is 51.6 minutes, and LMO is 55.8 minutes. The application of retention time recommendations for the separator can be done by optimizing the flow rate at 432,439 m3/day or adding new separator facilities that can accommodate operational volumes of up to 60.4 m3.